Photochemical reaction of Rh2(CO)4(μ-TPP)(TPP=tetraphenyl-porphyrinato) with pyridine (Py) in benzene. Generation of a mononuclear rhodium(II) porphyrin radical complex Rh(TPP)(Py) - Huang, J.-W. (2014)
10.1007/BF02910888